Analysis of QRQC Meeting Effectiveness Using The PDCA Method To Increase The Quality Rate in An Indonesian Automotive Company - Firman Firdaus; Wahyu Darmawan; Ferdian Setia Nugraha; Aldi Ilham Saputra; Yudi Prastyo (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Fierce competition within the automotive industry in Indonesia demands perfect quality standards, however, in reality, production lines frequently encounter efficiency constraints that result in a low quality rate. This research is motivated by the initial condition of an automotive company possessing a quality rate of 50%, where the quality problem-solving process remained reactive and unstructured. The purpose of this study is to evaluate the effectiveness of Quick Response Quality Control (QRQC) meetings through the integration of the Plan-Do-Check-Act (PDCA) method to increase the quality rate toward a maximum target of 100%. The research method employed is a case study approach featuring direct observations in the Genba area (the actual workplace) and the analysis of historical production data. The data processing results indicate that through a disciplined PDCA cycle—ranging from root cause identification using a Fishbone Diagram to the standardization of operational procedures—a significant improvement in quality performance was achieved. Post-implementation calculation data demonstrates an increase in the quality rate from 50% to 94.5%, alongside a reduction in problem-solving time from 3 days to a mere 4 hours. The discussion of the results indicates that the key to success lies in the synchronization between a rapid response on the production floor and the validation of physical data (real parts). The conclusion of this study confirms that implementing the PDCA method within the QRQC framework is not only effective in instantly rectifying product defects, but is also capable of establishing a sustainable mitigation system. Although the 100% target represents an operationally challenging achievement, this system has successfully steered the company out of its quality inefficiency zone.